Análisis de la energía incorporada de un edificio en altura en Uruguay - Pelufo Meier, Jose Pablo (2011)
Increasing global demand for energy, supplied primarily by polluting sources, generates severe environmental impacts. Buildings consume approximately 37 percent of total global energy, during the construction phase in the form of embodied energy and during the operation phase as operating energy. In Uruguay, current policies for energy efficiency are focused specifically on operational energy. On that basis, the present study intended to perform an energy analysis to assess the significance of embodied energy of a multi storied building in Uruguay compared to parameters of operational energy, and analyze traditional constructive alternatives in the most significant items. The methodology consisted of a process analysis on a selected building to calculate its initial embodied energy. Then recurrent and final embodied energy were estimated and on site collection of data was performed to assess operational energy, in the framework of a life cycle energy analysis. The survey included data on energy consumed by users for their own vehicles operation, which was used as a comparative parameter. Embodied energy was then compared to operational energy and energy payback period was calculated. Typical constructive alternatives were proposed for reinforced concrete structure and brick masonry. Initial embodied energy of alternatives was computed, and its impact on total embodied energy was assessed. Embodied energy values proved to be significant when compared with operational energy. Results showed that embodied energy was equivalent to about nineteen years of operation of the building, and twenty one years of users’ own vehicles fuel consumption. It was also concluded that the proposed alternatives for the structure did not represent a significant reduction, while for masonry meant a substantial decrease in total embodied energy. Finally lines of work were suggested for estimating carbon dioxide emissions derived from embodied energy, as well as for national data generation on materials energy intensities and materials replacement rates over the life of buildings, in order to improve life cycle energy analysis.